PENGEMBANGAN MEDIA INTERAKTIF BERBASIS POWERPOINT PADA MATA PELAJARAN MATEMATIKA MATERI PECAHAN KELAS IV SD NEGERI 1 PULAU PUNJUNG - Agus Saputra; Muhammad Subhan; Putri Ayuni (STKIP Subang, 2024)
This research is motivated by the lack of application and utilization of technological learning media, resulting in less than optimal achievement of learning objectives, especially in Mathematics subjects. An effort to overcome this problem is to innovate learning by utilizing technology to create interactive PowerPoint-based learning media that can be applied to mathematics subjects with fraction material and can be used easily to improve the quality of learning and achieve learning goals. This type of research is research and development. The development model used is a 4D development model which consists of the Define, Design, Develop and Disseminate stages. The trial was carried out on class IV homeroom teachers at SD Negeri 1 Pulau Punjung using data collection techniques through analysis of validity, practicality and effectiveness test data. The results of the research on the resulting PowerPoint interactive media obtained validation scores for materials, media and modules with an average score of 77.77 which was categorized as valid. The results of the practicality of PowerPoint-based interactive media obtained a score of 98.72 which was categorized as very practical. The results of the effectiveness of PowerPoint-based interactive media obtained a value of 81.81 which was categorized as very effective and the results of the effectiveness of distribution obtained a value of 82.98 which was categorized as very effective. So it can be concluded that the development of PowerPoint-based interactive media in the mathematics subject of class IV fractions at SD Negeri 1 Pulau Punjung is interesting and suitable for use and can continue to be developed as a learning medium.